(untitled) (Communications in Computational Chemistry, 2025)
Enzymatic carboxylation of phenols via the Kolbe-Schmitt reaction represents a promising sustainable strategy for CO_2 fixation and synthesis of high-value chemicals. This study investigates the reaction mechanism of 5-carboxyvanillate decarboxylase (LigW)-catalyzed carboxylation of non-natural monohydroxybenzoic acids, employing the quantum chemical cluster approach. First, we investigate the carboxylation mechanism of 4-hydroxybenzoate (4-HBA) to produce 4-hydroxyisophthalate (4-HIPA), a dicarboxylic acid with potent antioxidant and neuroprotective applications. The calculations reveal that the CO_2-binding mediates the preferred binding mode of the substrates and the incorporation of CO_2 to the active site favors the mode beneficial for the following reaction. The chemical reaction is initiated by the formation of a carbon-carbon bond between CO_2 and 4-HBA, followed by the rate-limiting proton transfer from the active site residue Asp314 to the resulting intermediate of the first step with a calculated barrier of 19.2 kcal/mol. Additionally, the potential of LigW in catalyzing the carboxylation of 3-hydroxybenzoate (3-HBA) is evaluated, and the calculations show that the reaction is energetically unfeasible due to the prohibitively high barrier of chemical steps. These mechanistic insights, together with the previous studies on the natural substrate, provide important information for the rotational design of LigW variants for industrial biocatalysis and CO_2 utilization.